Analysis of Environmental Risk Factors on Malaria Incidence in Fakfak Regency, West Papua - Nani Sri Untari; Mursid Rahardjo; Martini Martini (Eduvest - Journal of Universal Studies, 2024)
Malaria is still a significant problem in Indonesia due to its contagious nature, as it causes death, especially in children under the age of five. Based on 2019 data, there have been 409,000 deaths from malaria out of 229 million recorded malaria cases worldwide. WHO launched that in Indonesia there were 1,412 deaths from malaria from 811,636 new cases of malaria in 2021 in Indonesia. 89% of malaria cases in Indonesia occur in Papua Province. Fakfak Regency in 2023 will experience an increase in cases to 180 cases with API 2.2 per 1,000 population and still 50 Indigenous cases. This study aims to analyze the environmental factors that are most at risk for malaria incidence in Fakfak Regency, West Papua. Method: The study is observational with a Case-control research design. The 100 respondents used a total sampling consisting of 50 positive malaria cases with indigenous classification and 50 controls. Results: The most potential environmental risk factors for malaria incidence were the presence of breeding places with p-values of 0.000 and OR 13,903 (95%CI: 3,374-57,287), and night exit habits (p-value 0.045; OR 1,678). One important step is to break the chain of transmission by controlling environmental factors, namely the eradication of vector breeding sites, larvicide in puddles, cleaning of anopheles vector rest areas, the use of mosquito nets, Insect Residual Spraying (IRS), and other activities that can encourage the breaking of the chain of malaria transmission, which is carried out in an integrated manner by the community.